A robust optimization approach to multi-objective, multi-product and multi-period green supply chain network design by considering discount in uncertainty conditions - سیدحمیدرضا پسندیده; زهرا بهرامی; محمد محمدی (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2018)
Supply chain collaboration has been recognized as a potential business differentiator and a source of creating competitive advantage. One of the most common collaborations in the supply chain is vendor managed inventory. In this paper a vendor managed inventory system at two echelons with one vendor and multi retailers is studied. At this multi products system, goods are send to retailers cyclically. At reality, there is no exactness about available capacity of warehouses space and budget of both partners. Therefore stochastic constraints of warehouse space and budget are added to the model. The goal of the model is to minimize the total cost of the supply chain by optimizing the order quantity of each product for each retailer. At the end a numerical example of the model is solved by GAMS24.1.2 software. The sensitive analysis on the partnerؘs parameters cleared that the parameters of the vendor is more effective to mitigate the total cost of the supply chain.